Aqueous Extract of Salvia miltiorrhiza Bunge-Radix Puerariae Herb Pair Attenuates Osteoporosis in Ovariectomized Rats Through Suppressing Osteoclast Differentiation - Qin, Huan; Zhao, Wenwen; Jiao, Yang; Zheng, Haoyi; Zhang, Hao; Jin, Jingyu; Li, Qiu; Chen, Xiuping; Gao, Xia; Han, Yantao (Frontiers in Pharmacology, 2021)
Traditional herb pair Salvia miltiorrhiza Bunge-Radix Puerariae (DG) owns various biological activities including anti-inﬂammatory and anti-oxidative stress. Oxidative stress is one high-risk factor for osteoporosis, then effect of DG on osteoporosis and underlying mechanisms was explored both in vivo and in vitro. Firstly, the predication from network pharmacology hinted that DG has the potential for ameliorating osteoporosis. Consistent with predication, DG significantly restored bone loss and deficiency of type II collagen in femur, improved important characteristics of microarchitectural deterioration of tissue, reduced the numbers of NFATc1-positive osteoclast in the vertebra as well as decreased the serum osteoclast‐specific cytokine RANKL and OPG release in OVX rats exhibiting its protective effect against osteoporosis. In vitro, DG noticeably decreased osteoclastic-special marker protein expressions of RANK, c-Fos and NFATc1. Furthermore, autophagy pathway p62/LC3B, ROS production and NF-κB were all activated by RANKL stimulation and blocked by DG pretreatment. Moreover, autophagy inhibitors, ROS scavenger, Ca2+ chelator and NF-κB inhibitor remarkably suppressed c-Fos and NFATc1 expressions. Taken together, DG may ameliorate osteoporosis by regulating osteoclast differentiation mediated by autophagy and oxidative stress. This study provided a mechanistic basis for DG treating osteoporosis and offered a safe dose for DG in preventing and improving bone diseases.